Sally (Ship) certifications - Sally (Ship)
Certifications of the ship Sally, sailing out of Baltimore, Md., under command of John M. Hay, for Dutch and Danish ports.
Collection material in Dutch, with Danish.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hay, John M; Ship's papers -- 19th century; Baltimore (Md.) -- Commerce -- History -- 19th century; Denmark -- Commerce -- History -- 19th century; Netherlands -- Commerce -- History -- 19th century